Data of synthesis, characterization and luminescence measurements in 1D lanthanide coordination polymers based on lanthanides - D'Vries, Richard Fernando (2019)
In this work are presented all the conditions of synthesis explored to obtain a new family of compound with formula [Ln(4-OHBBA)3(H2O)2] (Ln= La, Pr). Powder X ray diffraction was used to identify the different phases obtained in the synthetic study. FT-IR spectroscopy and TG analysis for La and Pr pure phases are also reported. Optical properties of optically active CPs materials, solid state photoluminescence properties of La, Pr, La-(5%Eu) and La-(5%Tb) compounds were explored. We report the absorption, excitation and emission spectrum of the 4’-hydroxi-4-biphenylcarboxylic acid and a comparative description of the radiative (and noradiative) processes in solid state in Ln-(4-OHBBA) and Ln-BPDC compounds. Finally, a principal component analysis was conducted in order to take in account both signal contributions from the sensor (LCE at 384 nm and the europium emission at 610 nm) and for classifying the type of analytes used to test the sensing response of the materials.